Foundations of Culture of Peace and Peace Education as a means of Social Inclusion - Añaños, Fanny T.; Rivera, Maribel; Amaro, Ana (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
The aim of this paper is to provide a theoretical and grounded approach to the culture and peace education, both linked to socio-educational inclusion, as well as to the related processes and methods. This is an original proposal from pedagogical and social education approaches where inclusion, its principles, methods, and processes are merged together and applied to peace education in order to construct/deconstruct and promote a culture of peace. The method consisted of an exhaustive and specialized documentary study of written, virtual, and database sources with a subsequent content analysis.  The conclusions highlight the importance and applicability of the socio-educational approach, coherent with the social reality, especially of vulnerable and conflictive groups, where inclusion is a crucial element to improve the quality of life and social coexistence. It is also a practice that contributes to overcome risk factors and favours protective and potential situations.  All of the above will have an impact on the strengthening and improvement of  culture of peace as a tool for social and educational transformation, the protection of human rights, fair and sustainable development, management and transformation of  life conflicts in the most comprehensive and inclusive way possible, inside and outside the school context.